Diseminasi Media Edukasi Metode Pemeriksaan Payudara Sendiri (SADARI) sebagai Upaya Deteksi Dini Kelainan Payudara pada Siswi Sekolah Menengah Atas (SMA) di Kota Mataram - Herpan Syafii Harahap; Novrita Padauleng; Nurhidayati Nurhidayati; Yanna Indrayana (Universitas Mataram, 2020)
Breast cancer is one of the main women's health problem in the world, including Indonesia. Efforts to control this disease can be increased through education to the women community about the breast examination method named SADARI. This is simple but effective method to be used as a primary breast cancer prevention strategy. This method aims to find breast abnormalities routinely checked every month in women aged 18 and above. Therefore, educational efforts regarding the SADARI method for female high school students are expected to increase their knowledge about this method. The educational effort was carried out by disseminating information about SADARI method using poster media on female high school students in Mataram City. Pre-test and post-test are used to to evaluate the increase of their knowledge about the SADARI method. About 40 participants from SMAN 2, SMAN 3, SMAN 4, and SMAN 7 Mataram have participated in this dissemination activities of SADARI education method. There was an increase in student knowledge in the four high schools based on differences in the total mean pre-test and post-test scores (56 vs 82, p=0,000) as well as the average differences in each of the high schools, namely 58 vs 88 (SMAN 2); 50 vs 82 (SMAN 3); 52 vs 78 (SMAN 4); 64 vs 80 (SMAN 7). As many as 80% of students (32) experienced an increase in knowledge, and 20% did not show an increase in knowledge. This shows that this dedication activity can significantly increase students' knowledge about SADARI methods.